The Reformation in Private Towns in the Polish Crown in the 16th Century - Wijaczka, Jacek (Reformation & Renaissance review, 2021)
The article summarises the state of research concerning the Reformation in private towns in the Polish Crown (Kingdom). The main question considered is whether the noble town owners forced the inhabitants to accept the confession they themselves professed. The geographical scope of the article covers two provinces of the Crown: Greater Poland (Wielkopolska) and Lesser Poland (Małopolska), as in the third of them, Royal Prussia, there were no private towns in the 16th century.